Hazardous Elements of Green Manure-Ipomoea carnea - Adsul, Vaishali; Khatiwora, Eliza; Shah, Sapana; Deshpande, Nirmala (Asian Journal of Chemistry, 2010)
Ipomoea carnea (Mahananda in Marathi) is a native of South America and available abundantly in all the states of India due to its adaptation to the Indian climatic conditions. It belongs to convolvulaceae family and fistulosa subfamily. This non-woody plant can be successfully grown in temperate and tropical climatic conditions. It is frequently found in plains and lowlands near water sources. It is a narcotic hallucinogen, causes depression, general weakness, loss of body weight and death of animals after prolonged periods of plant intake. Taking this into consideration an elemental analysis was carried out. The qualitative and quantitative elements present in the leaves and stem of Ipomoea carnea was performed. It was found that the leaves and stem contain hazardous elements like lead, mercury and cadmium. Lead is absent in leaf while it is present in very low quantity in the stem. Mercury and cadmium are absent in the stem while these are present in the leaves. Amount of calcium present in the leaves is significantly higher as compared to all other elements and also that of stem.